Anarchist gospel [compact disc] - Sunny War (New West Records, 2023)
From her trials Sunny has crafted a set of songs that draw on a range of ideas and styles, as though she's marshaling all her forces to get her ideas across: ecstatic gospel, dusty country blues, thoughtful folk, rip-roaring rock n' roll, even avant-garde studio experiments. She melds them together into a powerful statement of survival, revealing a probing songwriter who indulges no comforting platitudes and a highly innovative guitarist who deploys spidery riffs throughout every song. Because it promises not healing but resilience and perseverance, because it doesn't take stuff for granted, this album holds up under intense emotional pressure, acknowledging the pain of living while searching for something that lies just beyond us, some sense of balance between the bad and the good.